Parallel agriculture:intelligent technology toward smart agriculture - Mengzhen KANG; Xiujuan WANG; Jing HUA; Haoyu WANG; Fei-Yue WANG (智能科学与技术学报)
Agricultural production is featured by strong uncertainty,diversity and complexity.Production benefit is related to natural conditions,national policies and market environment.Internet brings new challenges and chances to the management in agriculture.Generally speaking,smart agriculture refers to smart control on full production chain including management and service,using ICT techniques,in order to achieve high quality,high efficiency,security and controllability.Based on a brief introduction on the techniques related to these three aspects,the parallel agriculture as the methodology for decision support in smart agriculture was proposed,with artificial system for description intelligence,computational experiments for prediction intelligence,and parallel execution for prescription intelligence.Moreover,the link to agricultural enterprise resource planning (ERP) system,manufacturing execution system (MES) and process control system (PCS) was discussed.As China was developing large-scale agricultural production,methodology for managing scaled agriculture production was provided.